FAKTOR-FAKTOR IBU YANG BERHUBUNGAN DENGAN KEJADIAN ABORTUS - Rosi Kurnia Sugiharti (Viva Medika, 2009)
Maternal and perinatal mortality problem is a big problem in the world. It was reported that the maternal mortality caused by complications during pregnancy, childbirth, and postpartum. Abortion is one of the complications in pregnancy. Abortion related to various factors, maternal factors of 65%, 20% fetal factors, placental factors and 15%. Among these three factors, the cause of most of abortion is a maternal factors including age, parity, anemia, and maternal disease. Therefore, the authors wanted to know the relationship between maternal factors with the incidence of abortion. This research was conducted at the Mother and Child Hospital Amanah Sumpiuh using analytic correlational research design. Obtained total population of 350 respondents and a sampling technique used is total sampling. Data collection instrument in this study were the Medical Record. The results showed that the incidence of abortion in RSIA Amanah Sumpiuh in 2015 were 93 cases (26.6%). Addition of X2 statistical test results show that there is a significant relationship between age and parity with abortion and very low-level relationship with Chi Square values each X2 = 11.220 and X2 = 8.639. The coefficient of contingency both respectively 0.176 and 0.155. As for anemia and maternal illness, they do not have a significant relationship with the incidence of abortion. Keywords: Relationship, Mother Factor, abortion